2010
DOI: 10.1002/pi.2977
|View full text |Cite
|
Sign up to set email alerts
|

Toughening of in situ polymerized cyclic butylene terephthalate by addition of tetrahydrofuran

Abstract: A new method of toughening polymerized cyclic butylene terephthalate (pCBT) with tetrahydrofuran (THF) is proposed. The\ud pCBT was prepared by in situ ring-opening polymerization of a commercial cyclic butylene terephthalate, a cyclic form of\ud poly(butylene terephthalate), in the presence of THF. In comparison to conventionally polymerized pCBT, the resultant material\ud was found to be ductile, showing a strain at break of well above 100% in tensile tests. Other matrix properties, such as tensile\ud modulu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…However, the stiffness and strength were found to be decreased in these co-polyesters due to the properties of the co-polymers used. In the case of THF [33] and low molecular weight bi-functional epoxy resin [34], the resulted pCBT shows an increased ductility, with other important properties such as tensile strength, tensile modulus and glass transition temperature were not significantly altered. In a further attempt, physical modification was also done by adding carbon nanotubes (CNT) with content up to 0.1 wt.% [36].…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…However, the stiffness and strength were found to be decreased in these co-polyesters due to the properties of the co-polymers used. In the case of THF [33] and low molecular weight bi-functional epoxy resin [34], the resulted pCBT shows an increased ductility, with other important properties such as tensile strength, tensile modulus and glass transition temperature were not significantly altered. In a further attempt, physical modification was also done by adding carbon nanotubes (CNT) with content up to 0.1 wt.% [36].…”
Section: Introductionmentioning
confidence: 90%
“…Therefore, toughening of pCBT matrix has been attracted considerable attention, due to the increasing demand of high performance engineering thermoplastic composites [31][32][33][34][35][36]. There are usually two toughening approaches for pCBT matrix during isothermal production, including chemical modification by co-polymerization with soft polymers [32,34], organic solvent [33] and physical modification by addition of nanoparticles [36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…THF may have partially remained in the CBT blends after solvent blending, which can be explained by the fact that its chemical structure is similar to the one of the diol-derived portion in pCBT. It was shown that THF can lead to a pCBT with increased ductility but decreased stiffness and strength [38]. Finally, the sample pCBT100/PMDI/Cl30B 96/1/3-MB showed a stiffness and strength increase of ca.…”
Section: Tensile Propertiesmentioning
confidence: 97%
“…It has been reported that pCBT can be effectively toughened by the addition of tetrahydrofuran (THF) prior to polymerization. 91 The resultant pCBT was found to be tough, showing a strain at break of well above 100% in tensile tests.…”
Section: Adding Plasticizersmentioning
confidence: 98%